Ensuring Quality Instruction Amidst the Performance of Support and Core Functions of Faculty: Input for Establishing Workload Policy - Perez, Mark Jameson (Journal of Interdisciplinary Perspectives, 2025)
This sequential explanatory research design study aimed to determine the quality of instruction being facilitated by faculty with contract of service employment status. At the same time, they performed their support and core functions. The inputs served as a basis for establishing recommendations for a workload policy. The study involved 180 respondents and five participants affiliated with the state university, specifically in Region III. The researcher-designed questionnaires were used in this study to assess teaching performance, time management and workload balance, institutional support, job satisfaction and performance perception, administrative efficiency, and task management. Participants were asked about the factors that hinder them in delivering quality teaching and administrative performances. The results showed that COS faculty effectively deliver lessons and adapt teaching strategies to meet students’ needs. However, the additional and excessive workloads hinder their ability to provide timely feedback, maintain work-life balance, and innovate course materials. They can manage their tasks efficiently through delegation, but sometimes the teaching responsibilities are compromised due to limited institutional resources. Nevertheless, their contributions remain sustainable and impactful, ensuring they remain committed to delivering quality education and services. The findings revealed that multitasking impacts faculty teaching effectiveness due to limited resources, time constraints, compensation disparities, role conflicts, and administrative burdens. To address these issues, the faculty typically resorts to collaborative peer mentoring, stress management, time management, and mindfulness practices to stay focused. The study recommends regular training programs, provision of adequate resources, flexible scheduling, collaboration, performance-based incentives, and reduction of administrative tasks for faculty engaged in innovation, extension, research, and accreditation.